Radiation-induced synthesis of palladium nanoparticles immobilized on polypropylene non-woven fabric for catalysis application - Lopez, Girlie Eunice P. (Animo Repository, 2020)
A recyclable Pd-EDA-f-PP-g-PGMA catalytic system was synthesized using environment friendly gamma-induced reduction technique. In this work, Pd+2 wasreduced using Co-60 gamma source in the presence of ethylenediamine ligand- functionalized PP-NWF. Palladium nanoparticles were successfully immobilized and stabilized through the diamine ligand present on the fabric support as confirmed by XPS and FTIR. Curve fitting of the XPS spectra obtained three characteristic Pd components identified as the surface Pd0, bulk Pd0, and Pd+2. Moreover, the nanoparticle yield was found to increase with the radiation dose and the precursor concentration. Particles with diameter sizes of 8-31 ±5.4 nm, 14-59 ±11 nm, and 20- 157±30 nm were obtained for 2.0 mM, 4.0 mM, and 6.0 mM initial metal precursor concentration, respectively. The presence of large Pd clusters and broad size distribution of synthesized PdNPs may be attributed to the low dose rate that was used in this study. TGA analysis shows that the synthesized Pd-EDA-f-PP-g-PGMA has improved thermal stability, which can be suitable for applications such as catalysis in elevated temperature. The synthesized Pd-EDA-f-PP-g-PGMA was successfully applied as a catalyst in the reduction of 4-nitrophenol. Using 2.0, 4.0, and 6.0 mM initial Pd concentration, the Kapp was estimated to be 0.2015 min-1, 0.1807 min-1 , and 0.1237 min-1 , respectively and which are affected by the particle sizes. Recyclability experiment shows no significant decrease in catalytic activity with more than 90% conversion yield after five reaction cycles.